Antioxidant activities of some selected plants collected from Taman Negara / Siti Rahayu Mohd Zakria - Mohd Zakria, Siti Rahayu (Faculty of Applied Sciences, 2009)
This study was conducted to evaluate the antioxidative activity of methanolic extracts from different parts of twenty six plants collected from Taman Negara. Ethanol were used as solvents and antioxidative effects for lipid peroxidation measured by a ferric thiocyanate method (FTC) and thiobarbituric acid (TBA). About ten species of the plant were tested for their activity in inhibiting lipid peroxide, and most of them exhibited very strong antioxidant properties when compared to Vitamin E (α-tocopherol) and quercetin with percent inhibition of 81-98% in FTC and 89-97% in TBA assays. For free radical scavenging, DPPH method was performed to measure the activity of each species. Most of the species out of twenty six plants which were tested showed positive result for the different method which indicate the species contain a good antioxidant. From the part tested, most of positive result are leaves. The results suggest that several compounds contribute to antioxidative activity of different parts of the plants. The family of Annonaceae showed weak activity in free radical scavenging with the most species showed no activity or IC₅₀ value more than 100 µg/ml. The family of Melastomataceae showed strong in free radical scavenging which most of the part tested for every species give the value of IC₅₀ less than 30 µg/ml.